A Physical Computing Approach to the Introduction of Computer Programming among a Group of Pre-service Teachers - Govender, Reginald Gerald; Govender, Desmond Wesley (African Journal of Research in Mathematics, Science and Technology Education, 2021)
The emphasis on programming and robotics owing to the unfolding of the Fourth Industrial Revolution on the African continent has led the South African National Department of Education to propose a new subject in Grades R to 9. Hence, the training and development of pre-service teachers is crucial so that they can respond to the skills needed in the Digital Age. This preliminary study set out to explore and gauge pre-service teachers' experiences of programming and robotics. Programming is perceived as being difficult and challenging because of its abstract nature. Block-based programming has gained popularity in introducing the novice to programming concepts. This paper presents a case of nine computer science pre-service teachers from a South African university and their experiences of physical computer programming using Scratch for Arduino. Data was collected from unstructured observations during a practical session followed by a semi-structured group interview. The meaningful implementation of physical computing was supported by Rogers's (Freedom to learn: A view of what education might become, Charles Merrill, 1969) experiential learning theory. A prominent finding was that physical programming affords the opportunity to learn electronics and programming simultaneously, making programming relevant and interesting. Programming with Scratch for Arduino takes advantage of the fact that an Arduino is a physical device when paired with Scratch, further making these concepts accessible in a concrete manner.